MEDIA ULAR TANGGA DAN LITERASI: ANALISIS PENGARUH PADA MATERI MITIGASI BENCANA BANJIR PADA SISWA SEKOLAH MENENGAH PERTAMA - Kiki Septaria (JURNAL SPEKTRA, 2023)
The purpose of this study is to examine the validity of learning media in the design of snakes and ladders for disaster prevention and mitigation materials in junior high school in science education. The ADDIE approach was employed in the research, using two classes: the first trial class and the second test class (final implementation). This study's sample size was 25 students in the first trial class and 58 students in the second trial class. A validation questionnaire and a literacy test were used to collect data, which was then analyzed using statistical tests and SPSS software. The results show that the snake and ladder media developed are very valid (90 percent) of four expert validators, the literacy question instrument is valid (r-count > r table), and the results of the paired sample test show a significant effect on student disaster literacy (sig. 2 tailed 0.05). The snake and ladder media designs can be correctly applied and utilized on various catastrophe mitigation subjects. More study is needed to determine the relationship between students' disaster mitigation literacy and their enthusiasm for learning about disaster mitigation